Acequia La Chamba corredor urbano articulador del desarrollo en Guacarí Valle del Cauca. (2023)
The research project is geographically located in the municipality of Guacarí Valle del Cauca, where the research area is concentrated in the water ring of the La Chamba canal and its areas of influence.